(untitled) (Advancements in Homeopathic Research, 2022)
Introduction: Gastro intestinal diseases are the most common disorders seen worldwide. Microbiota is a term used for eukaryotic and prokaryotic microorganisms. In case of infected persons, it can produce symptoms like diarrhea, vomiting, nausea, flatulency, pain abdomen, inflammation of intestine, etc. The most common presentations of Gastro intestinal disorders are heart burn, nausea and vomiting, dysphagia, indigestion, chronic recurrent pain abdomen, flatulency, belching, loss of weight, etc. Homoeopathy is a system where symptom similiarity and individualization is considered in remedy selection.The vulnerability and frequency of disease will decrease when medicine prescribed is based on individualization. This is a retrospective study analyzing the previous case history to assess the efficacy of homoeopathy in gastrointestinal disorders. Materials and Methods: Case records of 261 patients diagnosed with gastrointestinal disorders with symptoms like pain abdomen, nausea, vomiting, heart burn, flatulence, diarrhea, bleeding per rectum, dysuria, hesitancy in urine etc. who had visited OPD of NHRIMH Kottayam Kerala from January 2022 to May 2022 (5 months) had been retrospectively analyzed to find out the most common gastrointestinal disorders and frequently indicated useful remedies in managing the patient. Results and Discussion It has been found that in our study maximum affection is in the age group of 51-60 and least in the age group of 91-100. Females were most affected than males. 45 new patients and 216 old patients had visited. The most common gastro intestinal disorders for which patients visited were Cholelithiasis, Gastritis and GERD.Most frequently indicated medicines were Nux vomica (20.69%), Sulphur (16.48%), Bryonia (9.96%), Argentum nitricum (9.58%) and Lycopodium (9.20%).The study showed drastic improvement in all the patients which proves that homoeopathy is highly effectivein gastrointestinal disorders. Conclusion From the above retrospective study, it is clear that when the homoeopathic principles were followed properly in treating a patient we can arrive at a permanent cure in all patients without any side effects.